2020
DOI: 10.1007/s00784-020-03257-w
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial and cytotoxic effects of a copper-loaded zinc oxide phosphate cement

Abstract: Objectives Evidence about modifications of dental luting materials to minimize biological failure at the "marginal gap" between teeth and fixed prosthodontics is scarce. We compared a copper-modified (Co-ZOP) and a conventional zinc oxide phosphate cement (ZOP) in terms of antimicrobial and cytotoxic potentials in vitro and in vivo. Materials and methods Specimens of ZOP and Co-ZOP were characterized by the mean arithmetic roughness (Ra) and surface free energy (SFE). Powder components were examined using scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Microbial adhesion was assessed in order to correlate fungal and bacterial colonization with surface characteristics and manufacturing methods. To ensure that only viable cells were subjected to the relative quantification of biofilm accumulation, a well-established, reproducible and highly sensitive ATP-based luminescence assay was performed [ 16 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial adhesion was assessed in order to correlate fungal and bacterial colonization with surface characteristics and manufacturing methods. To ensure that only viable cells were subjected to the relative quantification of biofilm accumulation, a well-established, reproducible and highly sensitive ATP-based luminescence assay was performed [ 16 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both microorganisms were harvested by centrifugation, washed twice with phosphate-buffered saline (PBS, Merck, Darmstadt, Germany) and resuspended in PBS. The suspensions of C. albicans or S. mutans in PBS were adjusted to an optical density of 0.3 at 600 nm by densitometry (Bio Photometer, Eppendorf, Hamburg, Germany) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some authors include endodontic complications, chipping and fracture of the porcelain, tooth fracture, periodontitis, and secondary caries at the tooth-material interface ( 3 , 4 ). The latter phenomenon is one of the main reasons for the failure of crown restorations ( 5 ). The key factors to ensure crowns’ longevity and clinical success are fracture resistance and marginal adaptation ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that calcium phosphate cement with copper phosphate nanoparticles could promote vascularized new bone formation around cancerous bone defects [ 90 , 91 ]. On the other hand, a copper-modified zinc oxide phosphate cement showed low surface allocations of copper but no improvement in its antimicrobial properties [ 92 ]. Therefore, with this limited study, it is difficult to justify the clinical application.…”
Section: Copper Nanoparticles In Dental Materialsmentioning
confidence: 99%